Healthy forests: sound economics, social justice - Vanclay, J.K.; Prabhu, Ravi (1998)
The paper outlines some of the key issues relating to the maintenance of 'healthy forests' in the tropics. It examines the concept of sustainable forestry and its corollary the destruction or degradation of forests, before moving on to discuss some of the challenges faced by the international community in trying to halt the destruction of tropical forests. The role of improved training and education, development of international standards for forest management and the reform of the forest management process and policy are discussed in this respect. The paper concludes that a more effective use of existing information is the first step and calls for immediate action on tropical forests.